Peran Google Form dalam Mendukung Evaluasi Pembelajaran di Era Digital - M. Alfaizh Anha Anha; M.Tengku Rahmadhani Tengku; Nadia Essa Putri Nadia; Zilmi Fitria; Zulfani Sesmiarni (Universitas Pahlawan Tuanku Tambusai, 2025)
The development of digital technology has significantly influenced the educational sector, particularly in the implementation of learning assessment. Evaluation is a fundamental component of the learning process as it serves to measure the achievement of learning objectives, students’ understanding levels, and the effectiveness of instructional strategies applied by educators. One of the digital tools widely utilized in assessment activities is Google Form. This article aims to examine the role of Google Form in supporting learning evaluation in the digital era through a comprehensive literature review. The method employed was a literature study by collecting data from scientific journals, reference books, and various relevant publications related to the use of Google Form as an assessment medium. The results of the review indicate that Google Form offers several advantages, including ease of access, flexible usage, time efficiency, and automated data processing features. Furthermore, Google Form enables educators to design diverse assessment instruments, provide prompt feedback, and manage assessment results systematically. From students’ perspectives, its use facilitates more practical and interactive evaluation experiences, contributing to increased motivation and engagement in completing assessment tasks. Based on these findings, it can be concluded that Google Form plays a strategic role as an effective digital-based assessment medium that aligns with the demands of modern education.